Pengaruh Penggunaan Media Pembelajaran E-Modul Informatika berbasis Android dengan Fitur Timbal Balik terhadap Hasil Belajar Siswa - Ilmi, Salma Maliki; Zaus, Mahesi Agni (TSAQOFAH, 2025)
This study examines the effect of using Android-based informatics e-modules with interactive features on student learning outcomes at SMK Negeri 9 Padang. A quantitative approach was employed using a quasi-experimental design involving two classes as the sample: an experimental class utilizing the e-module and a control class without it, each consisting of 30 students. The research instrument was a cognitive test comprising a pre-test and post-test. Data were analyzed using paired sample t-tests and independent t-tests. The results showed that the use of Android-based e-modules had a significant positive effect on improving learning outcomes, with the experimental class achieving a higher average post-test score of 88.3 compared to 79.0 in the control class, and a t-test significance value of 0.001 (< 0.05). These findings confirm that Android-based e-modules can serve as an effective alternative for enhancing the quality of learning in schools.